Monitoring the agri-food system in Myanmar: Food vendors - December 2021 survey round - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
This Research Note presents the results from a telephone survey with food vendors conducted in rural and urban zones throughout Myanmar and focuses on the results from the latest round completed in December 2021. The purpose of the survey is to provide data and insights to interested stakeholders in order that they better understand the effects of shocks related to COVID-19 and the ongoing political crisis on Myanmar’s food markets. In particular, the note explores COVID-19 prevention measures, changes in shopping behavior, difficulties in food vendor operations due to the COVID-19 and political crises, changes in availability and prices of foods, and perceived changes in consumption.